Corporate Social Responsibility - Al-ta’ie, Seham (Journal of Legal Sciences, 2022)
The social corporate responsibility give guidance principles to any Corporation in the world to take an effective rule in community by running their adhering in their business the principles of Transparency and fairness to the society and by Protecting the environment. Thus we can say that the Scope of the Social Corporate responsibility is: First deliver its services and sell its products in responsible manner, second: taking positive rule in enhancing the economic condition of its local community, i.e. where it operate its own businesses, Third: Taking effective rule in protecting the environment by not operating its own business in manner that might has negative implications on the environment.